English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

what are the steps to solve this?

2007-02-12 05:26:52 · 6 answers · asked by Anonymous in Science & Mathematics Mathematics

6 answers

Fix x and for h ≠ 0,

{f(x + h) - f(x)} / h

= {x + h - x} / h

= h / h = 1.

So the limit as h → 0 is 1.

2007-02-12 05:32:03 · answer #1 · answered by MHW 5 · 0 0

This is an example of a problem that seems too easy!

Basically, just plug in all the values shown, do some algebra, and you should see that when h or h^k , k positive appears in a numerator, its lim as h->0 is 0.

for f(x) = x
f(x+h) = x+h
f(x+h)-f(x) = h
then
[f(x+h)-f(x)]/h = h/h = 1
so lim is 1

Seems too easy, doesn't it?

note that this is the constant slope of your line y=x.

2007-02-12 13:31:40 · answer #2 · answered by modulo_function 7 · 0 0

This is the definition of the derivative. If you have already learned derivatives, you know the derivative of f(x) = x is f'(x) = 1. Otherwise,

lim h goes to 0 {(x+h) - x} / h = h/h = 1

2007-02-12 13:31:10 · answer #3 · answered by bozo 4 · 1 1

lim [f(x + h) - f(x)] / h
h -> 0

Since f(x) is given to be x, then
f(x + h) = x + h, and our limit becomes

lim [x + h - x]/h
h -> 0

Note that x and (-x) cancel each other out. This leaves us with

lim [h]/h
h -> 0

h/h is equal to 1.

lim 1
h -> 0

And the limit of a constant (since the variable h has disappeared) is just the constant itself.

lim 1 = 1
h -> 0

So the answer is 1.

2007-02-12 13:31:01 · answer #4 · answered by Puggy 7 · 0 0

lim(h to 0) [f(x+h)-f(x)]/h
= lim(h to 0) [(x+h)-x]/h
= lim(h to 0) h/h
= lim(h to 0) 1
= 1.

2007-02-12 13:29:58 · answer #5 · answered by Anonymous · 0 0

take the derivative

2007-02-12 13:30:18 · answer #6 · answered by bequalming 5 · 1 1

fedest.com, questions and answers